2003
DOI: 10.4102/sajip.v29i1.90
|View full text |Cite
|
Sign up to set email alerts
|

The construct validity of Schepers’ locus of control inventory for black and white tertiary students

Abstract: Popular criticism is that psychometric instruments, based largely on middle-class White values, knowledge and culture are biased and less valid for other population groups. It is therefore important that the testing of persons with highly dissimilar backgrounds receive greater attention. In this study the LCI of Schepers was applied to Black and White tertiary students to determine the construct validity of the instrument for different cultural groups. It was found that there is evidence of differences in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Although research has confirmed that some psychometric instruments developed in other countries are valid when applied in the South African context (Storm & Rothmann, 2003), there have also been multiple instances where instruments which were not adapted for use in the South African context resulted in difficulties with reliability and validity (Gray & Durrheim, 2006;Meiring et al, 2006). This can be attributed to the fact that an individual's subjective culture provides the basis through which they perceive their social environment, which in turn discourages certain behaviors and cultivates others (Anastasi, cited in Schaap, Buys, & Olckers, 2003). This affects how that individual interprets and responds to the questions posed by a measurement instrument (Prinsloo & Ebersöhn, 2002).…”
Section: Transfer Of Psychometric Instruments Across Different Culturesmentioning
confidence: 91%
“…Although research has confirmed that some psychometric instruments developed in other countries are valid when applied in the South African context (Storm & Rothmann, 2003), there have also been multiple instances where instruments which were not adapted for use in the South African context resulted in difficulties with reliability and validity (Gray & Durrheim, 2006;Meiring et al, 2006). This can be attributed to the fact that an individual's subjective culture provides the basis through which they perceive their social environment, which in turn discourages certain behaviors and cultivates others (Anastasi, cited in Schaap, Buys, & Olckers, 2003). This affects how that individual interprets and responds to the questions posed by a measurement instrument (Prinsloo & Ebersöhn, 2002).…”
Section: Transfer Of Psychometric Instruments Across Different Culturesmentioning
confidence: 91%
“…Table 3 provides a comparison of the current study to other published studies based on various South African groups. The comparisons made were with studies of different groups such as second year students (Schaap et al, 2003), third year students (Barends, 2004), working mothers (Herbst, Coetzee & Visser, 2007), employees from a financial institution head office (Gropp, Geldenhuys & Visser, 2007), community service doctors (Dhaniram & Cilliers, 2004), university administrative staff (Cilliers & Ngokha, 2006), middle managers from a nature reserve organisation (Marais, 1997) and middle managers from a semi-governmental organisation (Cilliers & Coetzee, 2003). In the study of Schaap et al (2003) the second year student group was divided by race with group 1 being Black students and group 2 being White students.…”
Section: Resultsmentioning
confidence: 99%
“…The 26 item Rotter's (1966) generalised locus of control scale (construct validity. 80 and Cronbachalpha reliability .88) as cited in Schaap et al (2003)was used to measure the participants' locus of control.…”
Section: Methodsmentioning
confidence: 99%
“…Such an expectation makes internals to invest seriously in education by working hard. Consequently, a student with an internal locus of control will adopt a positive attitude towards hard work for a better academic achievement (Schaap et al, 2003). Meanwhile a student with an external locus of control will attribute his or her academic struggles to other people and fate, and hence adopt a negative attitude (Schaap et al, 2003).…”
Section: Levels Of Locus Of Control and Academic Attitudes Among Univmentioning
confidence: 99%